数列{an}的通项公式为an=
(1)求f(1)、f(2)、f(3)、f(4)的值; (2)求f(n)的表达式; (3)数列{bn}满足b1=1,bn+1=2f(n)-1,它的前n项和为g(n),求证:当n∈N*时,g(2n)-
|
(1)f(1)=
,f(2)=3 4
,f(3)=2 3
,f(4)=5 8
.3 5
(2)由f(n)=(1-a1)(1-a2)…(1-an)
得:f(n-1)=(1-a1)(1-a2)…(1-an-1)(n>1),
两式相除得:
=1-an=1-f(n) f(n-1)
=1 (n+1)2
(n>1).n(n+2) (n+1)2
∴f(n) f(n-1)
…f(n-1) f(n-2)
=f(2) f(1) n(n+2) (n+1)2 (n-1)(n+1) n2
…n(n-2) (n-1)2
,2×4 32
=f(n) f(1)
•n(n-1)(n-2)…2 (n+1)n…3
=(n+2)(n+1)…4 (n+1)n…3
•2 n+1
,n+2 3
∴f(n)=
(n>1),又f(1)=n+2 2(n+1)
适合此式,3 4
∴f(n)=
.n+2 2(n+1)
(3)b n+1=2f(n)-1=
,1 n+1
g(n)=1+
+1 2
+…+1 3
,1 n
∴g(2n)=1+
+1 2
+…+1 3
.1 2n
设∅(n)=f(2n)-
,n 2
则∅(n)=1+
+1 2
+…+1 3
-1 2n
.n 2
∅(n+1)-∅(n)=1+
+1 2
+…+1 3
-1 2n+1
-(1+n+1 2
+1 2
+…+1 3
-1 2n
)n 2
=
+1 2n+1
+…+1 2n+2
-1 2n+1
.1 2
∵
+1 2n+1
+…+1 2n+2
的项数为2n,1 2n+1
∴
+1 2n+1
+…+1 2n+2
>1 2n+1
+1 2n+1
+…+1 2n+1
=1 2n+1
×2n=1 2n+1
,1 2
∴∅(n+1)-∅(n)>0.即数列{∅(n)}是单调递增数列.
其最小值为∅(1)=g(2)-
=11 2
∴∅(n)≥1即g(2n)-
≥1.n 2